Anregungen aus dem Postkolonialitätsdiskurs für das Interreligiöse Lernen: Religionswissenschaftliche und religionspädagogische Überlegungen - Koch, Anne (Österreichisches Religionspädagogisches Forum, 2023)
Only recently, questions were raised of how concepts in interreligious education may better account for configurations of power and hegemony and findings from the postcolonial/decolonial debate. To answer to this lacuna, we combine the perspectives of study of religion and religious education and learn from milestones of respective debates. It is our goal to suggest more appropriate ways of interreligious learning and teaching and to engage many-voiced and critically towards powerful representations and hegemonial structures within religious plural contexts.